Interphase cohesin regulation ensures mitotic fidelity after genome reduplication - Stormo, Benjamin M. (Mol Biol Cell, 2019)
To ensure faithful genome propagation, mitotic cells alternate one round of chromosome duplication with one round of chromosome separation. Chromosome separation failure thus causes genome reduplication, which alters mitotic chromosome structure. Such structural alterations are well documented to impair mitotic fidelity following aberrant genome reduplication, including in diseased states. In contrast, we recently showed that naturally occurring genome reduplication does not alter mitotic chromosome structure in Drosophila papillar cells. Our discovery raised the question of how a cell undergoing genome reduplication might regulate chromosome structure to prevent mitotic errors. Here, we show that papillar cells ensure mitotic fidelity through interphase cohesin regulation. We demonstrate a requirement for cohesins during programmed rounds of papillar genome reduplication known as endocycles. This interphase cohesin regulation relies on cohesin release but not cohesin cleavage and depends on the conserved cohesin regulator Pds5. Our data suggest that a distinct form of interphase cohesin regulation ensures mitotic fidelity after genome reduplication.